Intervention among Suicidal Men: Future Directions for Telephone Crisis Support Research - Hunt, Tara; Wilson, Coralie J.; Woodward, Alan; Caputi, Peter; Wilson, Ian (Frontiers in Public Health, 2018)
Telephone crisis support is a confidential, accessible, and immediate service that is uniquely set up to reduce male suicide deaths through crisis intervention. However, research focusing on telephone crisis support with suicidal men is currently limited. To highlight the need to address service delivery for men experiencing suicidal crisis, this perspective article identifies key challenges facing current telephone crisis support research and proposes that understanding of the role of telephone crisis helplines in supporting suicidal men may be strengthened by careful examination of the context of telephone crisis support, together with the impact this has on help-provision for male suicidal callers. In particular, the impact of the time- and information-poor context of telephone crisis support on crisis-line staff’s identification of, and response to, male callers with thoughts of suicide is examined. Future directions for research in the provision of telephone crisis support for suicidal men are discussed.